Studying the Same-Gender Preference as a Defining Feature of Cultural Contexts - Bukowski, William M.; DeLay, Dawn (Frontiers in Psychology, 2020)
Research on culture would be enriched by studying the connection between gender and peer relations. Cultures vary in the roles, privileges, opportunities and rights that are ascribed to females and males. They are known to differ also in the degree to which females and males interact with each other. Although the preference for same-gender peers has been observed across multiple cultural contexts, the degree of this segregation between females and males varies. We argue that variability in the interactional divide between females and males is an important cultural construct that is likely to account for diversity in developmental processes and outcomes.